TEKNIK VOKAL DALAM MENYANYIKAN BUKU ENDE BAGI SONG LEADER DI GEREJA HKBP SUKADAME PEMATANGSIANTAR - Jubelando O Tambunan (Gondang: Jurnal Seni dan Budaya, 2021)
This study is to find out the vocal technique abilities that are possessed by the song leaders of HKBP Church of Sukadame Ressort Sukadame Pematangsiantar to sing out songs in Buku Ende and to identify the proper vocal techiques that need to be improved and mastered by the songleaders. Song leaders usually take part in most HKBP church services. They help the congregation to sing out the songs of Buku Ende by leading them to sing in the correct tunes as written in the book. As one of the main book songs that is used in churches’ services by HKBP including HKBP Sukadame of Ressort Sukadame Pematangsiantar, Buku Ende must be sung correctly in the correct tunes and manner so that the messages of the song can be conveyed correctly to glorify God to the max.. Therefore, the churches’ song leaders are expected to have the good vocal techniques. The study is conducted by using a descriptive qualitative research method. The data were collected through observation, interview, and documentation. This study reveals that the vocal tehcnique abilities that are possessed by the song leaders of HKBP Sukadame of Ressort Sukadame Pematangsiantar need to be improved by conducting a vocal training. The vocal technique abilities that are necessary to be trained such as breathing technique, songs’ intonation, producing the vocal resonance and phrasin techniques. These vocal techniques are necessarily mastered by the song leaders in order to be able to sing and lead the congregation to sing out the songs in Buku Ende in correct tunes and manner to worship the God so that the worship services could run well. Keyword: vocal technique, song leader, Buku Ende